THE EQUIVALENTS OF WISH IN INDONESIAN - Sukarsih, Engkay; Sujana, Sujana (UG Journal, 2012)
The writer took 'The equivalents of wish in Indonesian' as the problem of theresearch. The writer chose this topic because the writer was interested to find outthe equivalents of wish. The aim of this research was to find out the equivalentsof wish in Indonesian. In this research, the writer used qualitative method. Themethod covered collecting, arranging, classifying, analyzing, and interpreting thedata. All the data were taken from novels by Stephenie Meyer entitled 'New Moon','Eclipse' and 'Breaking dawn'. From the 100 data of wish, the writer classifiedthem into their translation. The result of the research showed that wish aretranslated into seandainya(saja), kalau(saja), harap, berharap, berharap kalausaja, ingin, semoga and zero translation. There are 43% of wish are translatedinto 'kalau(saja)', 31% are translated into 'berharap', 7% are translated into'berharap kalau saja', 6% are translated into 'seandainya(saja), 4% are translatedinto 'ingin', 4% are translated into 'harap', 1% is translated into 'semoga' and 4%are not translated or zero translation.